MiR-1 downregulation correlates with poor survival in clear cell renal cell carcinoma where it interferes with cell cycle regulation and metastasis - Xiao, Haibing (Oncotarget, 2015)
MicroRNAs (miRNA) that are strongly implicated in carcinogenesis have recently reshaped our understanding of the role of noncoding RNAs. Here, we focused on the function and molecular mechanism of miR-1 and its potential clinical application in clear cell renal cell carcinoma (ccRCC). First, miR-1 was signiﬁcantly downregulated in 87.8% renal cancer samples compared with corresponding noncancerous tissues (NCT), which was significantly associated with clinical stage, T classification and poor overall survival. Functional study demonstrated that enforced overexpression of miR-1 in renal cancer cells inhibited proliferation and metastasis in vitro and in vivo. Conversely, miR-1 inhibitor silencing miR-1 expression promoted cell proliferation and metastasis in ccRCC. CDK4, CDK6, Caprin1 and Slug were each directly targeted for inhibition by miR-1 and restoring their expression reversed miR-1-mediated inhibition of cell cycle progression and metastasis. Taken together, our findings established a tumor suppressive role for miR-1 in the progression of ccRCC by targeting CDK4, CDK6, Caprin1 and Slug and suggested miR-1 can be served as a novel potential therapeutic target for ccRCC.